New Identity and Formulas for Solving Mathematical Problems - Saini, D.P. (SCHOOL SCIENCE, 2025)
From time to time, discoveries are made whenever problems arise. This mentioned identity is discovered by me to solve the mathematical problem, Beal conjecture. Beal conjecture is Fermat’s last Theorem (Fit). Beal’s conjecture is, if Ax + By = z where A, B, C, x, y and z are positive integers and x, y and z are greater than 2, then A, B and C must have a common prime factor.